Mouse protamine 2 is synthesized as a precursor whereas mouse protamine 1 is not. - Yelick, P C (1987)
The nuclei of mouse spermatozoa contain two protamine variants, mouse protamine 1 (mP1) and mouse protamine 2 (mP2). The amino acid sequence predicted from mP1 cDNAs demonstrates that mP1 is a 50-amino-acid protein with strong homology to other mammalian P1 protamines. Nucleotide sequence analysis of independently isolated, overlapping cDNA clones indicated that mP2 is initially synthesized as a precursor protein which is subsequently processed into the spermatozoan form of mP2. The existence of the mP2 precursor was confirmed by amino acid composition and sequence analysis of the largest of a set of four basic proteins isolated from late-step spermatids whose synthesis is coincident with that of mP1. The sequence of the first 10 amino acids of this protein, mP2 precursor 1, exactly matches that predicted from the nucleotide sequence of cDNA and genomic mP2 clones. The amino acid composition of isolated mP2 precursor 1 very closely matches that predicted from the mP2 cDNA nucleotide sequence. Sequence analysis of the amino terminus of isolated mature mP2 identified the final processing point within the mP2 precursor. These studies demonstrated that mP2 is synthesized as a precursor containing 106 amino acids which is processed into the mature, 63-amino-acid form found in spermatozoa.